Rectification of cast through foam-ceramic filters is an effective method of metal quality improvement - A. N. Leonov; O. L. Smorygo; M. M. Dechko; A. I. Marukovich (Литьë и металлургия)
The article presents comparative analysis of various classes of sponge permeable materials according to their structural, hydrodynamic, physicomechanical and filter characteristics. It is shown that foam-ceramic filters are most effective for rectification of metal alloys of nonmetal lie inclusions.